Mechanistic subtypes of focal right ventricular tachycardia. (9th May 2018) - Lerman, Bruce B.; Cheung, Jim W.; Ip, James E.; Liu, Christopher F.; Thomas, George; Markowitz, Steven M.
Abstract: Idiopathic sustained focal right ventricular tachycardia (VT) is most frequently due to outflow tract (OT) tachycardia. This arrhythmia is recognized by its characteristic ECG pattern and sensitivity to adenosine. However, there are other forms of idiopathic, focal sustained VT that originate from the right ventricle (RV), which are less well appreciated and easily overlooked. This review will identify the characteristic features and electrophysiologic properties of these forms of RV VT, including those originating from the tricuspid annulus, right ventricular papillary muscles, and moderator band as well as variants of classic RVOT tachycardia and those due to microreentry in the presence of preclinical disease. Recognition of these subtypes of focal RV tachycardia should facilitate targeted therapy.